2018
DOI: 10.1177/1524838018781104
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women in Turkey: A Social Ecological Framework of Determinants and Prevention Strategies

Abstract: Violence against women (VAW) in Turkey is concerning, and to develop and implement effective prevention strategies for addressing it, careful consideration must be given to the factors that influence it. In this review, we synthesized the body of literature on VAW in Turkey according to a social ecological framework, which is a theoretical model considering the complex interplay between individual, relationship, community, and societal factors. Consistent with this framework, we obtained research articles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 87 publications
0
27
0
2
Order By: Relevance
“…Tables 1 and 2 summarize the result of literature review. (50). Young age in marriage leads to increased exposure to violence due the husband is superior to the women (51).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarize the result of literature review. (50). Young age in marriage leads to increased exposure to violence due the husband is superior to the women (51).…”
Section: Resultsmentioning
confidence: 99%
“…The three dimensions of this level are: multiple partners, arranged or forced marriages relationship satisfaction and marital con ict. Communication skills training programs focusing on culturally appropriate con ict management should be designed for couples (50). Experts and health care providers have identi ed several bene ts of using remote support, such as dealing with isolation, reducing deterrence, fear and embarrassment, and enhancing victims' empowerment (3).…”
Section: Resultsmentioning
confidence: 99%
“…[10] Lack of support from intimate partner, family, and community is also reported in other studies. [1025] The results also showed that most intimate partners did not provide their wife with financial support. This finding is in agreement with those of other studies.…”
Section: Discussionmentioning
confidence: 98%
“…The subordination of women in Turkey is particularly severe because of the influences of religious traditions as well as social and political practices (Tekkas Kerman & Betrus, ). Sexist discourse by politicians in Turkey, such as “men and women are not equal from their creation,” continues to produce inequality between women and men and support sexist attitudes towards women (Agence France‐Presse in Istanbul, ).…”
Section: Literature Reviewmentioning
confidence: 99%